Scheduling Automated Guided Vehicles considering transport load transfers - Patrick Boden; Sebastian Rank; Thorsten Schmidt (Logistics Research, 2023)
This paper investigates a scheduling approach for Automated Guided Vehicle Systems, enabling transport load transfers between vehicles during transport execution. The vehicles can use predefined transfer stations to buffer transport loads until the transport continues by a following vehicle. The objective is to improve system performance by decreasing vehicle utilization to yield higher throughput. Transfer operations are planned ad-hoc depending on the current system state. We describe the task assignment as a Pickup and Delivery Problem with Transfers. Since the problem is classified as NP-hard, an Adaptive Large Neighborhood Search heuristic is given. Test instances and a material flow simulation study evaluate that transport load transfers potential for improvement depends significantly on the characteristics of the transport system.
Keywords: 650; Transport Load Transfers; Automated Guided Vehicles; Task Assignment; Scheduling; Pickup and Delivery Problem with Transfers